Aid programme of the neutrals - Jürgen M. Bartsch (Intereconomics, 1971)
Foreign aid has often been considered as one aspect of the world-wide confrontation between East and West and one might therefore wonder to what extent the neutral European countries have an aid policy of their own reflecting their status of non-alignment. The following article tries to give an answer to this question by analysing the aid policies and efforts of Austria, Finland, Sweden and Switzerland.
Keywords: 330; Development Policy